Socialist worldmaking: The political economy of urban comparison in the Global Cold War. (June 2022) - Stanek, Łukasz
This article revisits comparative urban studies produced during the Cold War in the framework of 'socialist worldmaking', or multiple, evolving and sometimes antagonistic practices of cooperation between socialist countries in Eastern Europe and decolonising countries in Africa and Asia. Much like the recent 'new comparative urbanism', these studies extended the candidates, terms and positionalities of comparison beyond the Global North. This article focuses on operative concepts employed by Soviet, Eastern European, African and Asian scholars and professionals in economic and spatial planning across diverse locations, and shows how they were produced by means of 'adaptive' and 'appropriative' comparison. While adaptive comparison was instrumental in the application of Soviet concepts in countries embarking on the socialist development path, appropriative comparison juxtaposed concepts from various contexts – whether the 'West' or the 'East' – in order to select those best suitable for the means and needs on the ground. This article argues that this conceptual production was conditioned by the political economy of socialist worldmaking and shows how these experiences are useful for a more critical advancement of comparative urban research today.